Design of effective energy efficiency policies. An analysis in the frame of target setting, monitoring and evaluation. - Schlomann, Barbara (Fraunhofer Verl., 2014)
Energy efficiency is widely acknowledged as the most important strategy for achieving global energy and climate targets. Apart from its contribution to the reduction of energy consumption and energy-related greenhouse gas emissions (GHG), improving energy efficiency can deliver a range of co-benefits to the economy and society. There are, however, indications that energy efficiency policy is still insufficiently anchored both in the EU and many Member States as well as at an international level. This thesis focuses on the question how to create more favourable preconditions for an effective anchoring of energy efficiency policy in energy and climate policy. The design of energy efficiency policies is analyzed in the frame of the setting of energy efficiency targets and the monitoring and evaluation of their success. This provides new insights in the functioning of policies and hence their improvement in view of target achievement.
Keywords: Energie; Energiepolitik; Energieverbrauch; Energieeinsparung; Umweltpolitik; Klima; Überwachung; Bewertung; Klimaschutzziel; Energieeffizienz; Emissionshandel; Politikziel; Politikinstrument